Designing a Software to Count the Body Composition and Somatotype and its Role in Pursing the Morphological State of Spotsmen - عطا الله, أحمد; عسلي, حسين; زرقين, سادق (My University, 2015)
Designing a software to count the body composition and somatotype and its role in pursing the morphological state of sportsmenThe objective from this study is to design a software which relies on the Heat-Carter method for onthropometrie somatotype and matiegka équation in counting the body mass (the fat, the muscle, the bones)and among the characteristics of the software:1.Facilitating the countable operations for matiegka équations and Heat-carter method for antropometric somatotype.2.Counting the results of the body mass and somatotype for big number of sportsmen in short period of time,less effort and more accuracy.3.Designing basic data rich of the body mass ‘and the somatotype ‘s r sults of many sportsmen,So that,it helps in pursing their morphological state and the way to select and guid them to the be t sport activity.4.Designing the somatochart and diagram for body composition.As a future study we are loaking for luiking the software with the electronie side in order to design an outomatic machine which works on taking the anthropometric measurments in human body with high accurary and to transmit the data to the countable machine in which they will be treated and stored in basic data otomatically.
Keywords: Designing a Software to Count the Body Composition and Somatotype and its Role in Pursing the Morphological State of Spotsmen